DETECTION OF MYCOPLASMA SYNOVIAE ANTIBODIES IN SERA OF BROILER CHICKENS BY THE ELISA - Iancu, I.; Cătană, N.; Popa, V.; Degi, J.; Pascu, C.; Herman, V.; Ilgekbayeva, G. (Scientific Journal of Pedagogy and Economics, 2020)
Mycoplasma synoviae (MS) infection most frequently occurs as a subclinical respiratory infection. Approximately 2-4 weeks are required for antibodies to develop in infected birds. Clinical examination was made daily, in broilers after 10 days old, because at this age there were seen the first symptoms of disease. Enzyme-linked immunosorbent assay is commonly used as a diagnostic test and for routine testing of flocks and may replace serum plate agglutination as the primary serologic test. The serologic exam carried out through ELISA test at 21 and 35 days evidenced the specific antibodies and sero-conversion phenomenon. At 21 days old (B I), 22, 91% from the analysed sera were positive, and at 35 days old (B II), 26,66% were positive, until the age for slaughter (42 days). The value of titrers geometrical mean of 10,92 times higher at 35 days old than at 21 days old and the higher proportion of the obtained positive titrers, reveal both the implication of M. synoviae in the etiology of disease, and her infectiousness, by horizontal transmission.